2014
DOI: 10.3957/056.044.0210
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Importance of Trophy Harvest and Retaliatory Killing of Large Carnivores: South African Leopards as a Case Study

Abstract: There are considerable challenges in the conservation of large carnivores, caused by large area requirements, low reproduction rates and low population densities coupled with their tendency to cause conflict with humans. Trophy hunting is one strategy to increase support for large carnivore conservation. Leopards, Panthera pardus, rank among the most soughtafter trophies in South Africa. However, trophy hunting has been suggested as partly responsible for leopard population declines, and leopards are also kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…This is troubling as (a) this is considerably below the 'safe-age' limit for hunting set by Packer et al (2009) and (b) outfitters typically advertise their best trophies on websites, and it is likely that a high proportion of younger animals are under-represented. The results from our assessment of leopard trophies on outfitter websites lend support to the findings of Spong, Hellborg & Creel (2000) and Swanepoel et al (2014) who also found a high proportion of sub-optimal animals (mainly females) inharvests of leopards in Tanzania and South Africa.…”
Section: Conservation Implicationssupporting
confidence: 76%
See 3 more Smart Citations
“…This is troubling as (a) this is considerably below the 'safe-age' limit for hunting set by Packer et al (2009) and (b) outfitters typically advertise their best trophies on websites, and it is likely that a high proportion of younger animals are under-represented. The results from our assessment of leopard trophies on outfitter websites lend support to the findings of Spong, Hellborg & Creel (2000) and Swanepoel et al (2014) who also found a high proportion of sub-optimal animals (mainly females) inharvests of leopards in Tanzania and South Africa.…”
Section: Conservation Implicationssupporting
confidence: 76%
“…However, using trophy hunting for revenue generation can create conflicts of interest whereby wildlife authorities tend to set quotas at high levels to maximize their income (Nelson et al, 2013;Lindsey et al, 2014). Excessive quotas can lead to population declines which can be compounded by other forms of mortality, such as non-parental infanticide (Loveridge, Searle, Murindagomo & Macdonald, 2007;Balme, Slotow & Hunter, 2009;Swanepoel, Lindsey, Somers, van Hoven & Dalerum, 2014). Excessive off-takes in hunting blocks can also result in negative impacts on populations in adjacent fully protected areas (Balme et al, 2010).Trophy hunting may also have genetic impacts over time and lead to a decrease in the size of the heritable secondary sexual traits selected for by hunters (Coltman et al, 2003;Von Brandis & Reilly, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although legal persecution usually is controlled, it is sometimes carried out to cause local population extinction (Hone, 2004). Illegal persecution can potentially have dramatic effects on local populations, since it is often carried out on endangered species that reside in small populations (Treves and Karanth, 2003;Swanepoel, Lindsey, Somers, Van Hoven and Dalerum, 2014).…”
Section: Motivational Drivers Behind Huntingmentioning
confidence: 99%